2012
DOI: 10.1186/cc11298
|View full text |Cite
|
Sign up to set email alerts
|

GABA receptor ameliorates ventilator-induced lung injury in rats by improving alveolar fluid clearance

Abstract: IntroductionMechanical ventilators are increasingly used in critical care units. However, they can cause lung injury, including pulmonary edema. Our previous studies indicated that γ-aminobutyric acid (GABA) receptors are involved in alveolar-fluid homeostasis. The present study investigated the role of GABA receptors in ventilator-induced lung injury.MethodsAdult female Sprague-Dawley rats were subjected to high-tidal-volume ventilation of 40 ml/kg body weight for 1 hour, and lung injuries were assessed.Resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 56 publications
0
22
0
Order By: Relevance
“…While NO-ergic mechanism may have a limited contribution, the GABA-ergic mechanism in the posterior hypothalamus has a significant role to play in alleviating pulmonary edema. It is interesting to mention here that in rats, intratracheal administration of GABA has already been reported to reduce the pulmonary edema associated with ventilator induced lung injury by promoting alveolar fluid clearance mechanisms (Chintagari and Liu, 2012). The present findings demonstrate that central GABA has an additional beneficial effect in the pulmonary edema associated with hypobaric hypoxia namely a reduction in pulmonary vascular permeability as evidenced by a decrease in Evans blue leakage.…”
Section: Effect Of Snapmentioning
confidence: 61%
“…While NO-ergic mechanism may have a limited contribution, the GABA-ergic mechanism in the posterior hypothalamus has a significant role to play in alleviating pulmonary edema. It is interesting to mention here that in rats, intratracheal administration of GABA has already been reported to reduce the pulmonary edema associated with ventilator induced lung injury by promoting alveolar fluid clearance mechanisms (Chintagari and Liu, 2012). The present findings demonstrate that central GABA has an additional beneficial effect in the pulmonary edema associated with hypobaric hypoxia namely a reduction in pulmonary vascular permeability as evidenced by a decrease in Evans blue leakage.…”
Section: Effect Of Snapmentioning
confidence: 61%
“…Thus, both ENaC and Na,K-ATPase are accredited with key roles in the resolution of pulmonary edema (10). Several recent in vivo studies have demonstrated vasopressin-2 receptor antagonist (11), GABA receptor (12), b-adrenergic (13), triiodo-L-thyronine (14), and leukotriene D 4 (15) could markedly upregulate AFC in experimental animal models. We previously reported that treatment with lipoxin A 4 , an anti-inflammatory and proresolution mediator, and lipoxin receptor agonist (BML-111) significantly stimulated AFC in oleic acid-induced lung injury and decreased pulmonary edema (16).…”
mentioning
confidence: 99%
“…However, 1 possible link is the pulmonary γ-aminobutyric acid type A (GABA A )-receptor (GABAAR). 38 Current studies suggest that modifying or blocking GABAAR might lead to an improved alveolar fluid clearance in ALI 39 and that GABAAR function may be modulated by isoflurane. 39 Further work is needed to better understand the role of GABAAR in volatile-mediated immunomodulation and alveolar fluid clearance.…”
Section: Discussionmentioning
confidence: 99%
“…38 Current studies suggest that modifying or blocking GABAAR might lead to an improved alveolar fluid clearance in ALI 39 and that GABAAR function may be modulated by isoflurane. 39 Further work is needed to better understand the role of GABAAR in volatile-mediated immunomodulation and alveolar fluid clearance. Another potential mediator for the sevoflurane effect we observed is downregulation of toll-like receptor 2 and toll-like receptor 4 resulting in an attenuation of proinflammatory cytokines.…”
Section: Discussionmentioning
confidence: 99%